Temperature dependent characteristics of InAlN/GaN HEMTs for mm-wave applications - Xing, Weichuan (2018)
This work presents a 100 nm-gate InAlN/GaN HEMT with current-gain cutoff frequency (fT) up to 120 GHz at room temperature (25 °C). Temperature dependent DC and RF characteristics are measured from 25 °C to 200 °C. The maximum drain current (Id−max) decreases from 1247 mA/mm to 927 mA/mm as the temperature increases from 25 °C to 200 °C. For maximum fT, it drops to 87 GHz and 64 GHz at 100°C and 200°C respectively. These results show that although both DC and RF performances decrease with the increase in temperature, the device still exhibits high mm-wave performance at high temperatures. Thus, InAlN/GaN based HEMTs are very promising for high temperature mm-wave applications.